2009
DOI: 10.1186/bf03352972
|View full text |Cite
|
Sign up to set email alerts
|

Shear-wave anisotropy beneath the Ryukyu arc

Abstract: We have investigated regional shear-wave splitting beneath the Ryukyu arc in order to clarify the mantle flow beneath the Ryukyu arc and compare it with the extension of the Okinawa Trough. The splitting of regional shear waves (direct S) in the central and southern Ryukyu arc regions was analyzed in terms of fast-polarization direction and delay time using data from 11 short-period stations and two broadband seismic stations. The events occurred at depths ranging between 45 and 217 km, and the magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our trial‐and‐error modeling procedure closely follows that used by Wirth and Long []. While our starting isotropic model matched the radial component receiver functions well, we were unable to match features on the transverse component data that arrive between 3–6 s. We added a layer of anisotropy in the wedge mantle with a trench‐parallel fast symmetry axis, as inferred from previous studies [e.g., Long and van der Hilst , ; Nakamura and Yamamoto , ]. Although this feature improved the fit, we were unable to identify a combination of anisotropy parameters for the wedge mantle portion of our model that allowed us to reproduce all the transverse component features.…”
Section: Forward Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Our trial‐and‐error modeling procedure closely follows that used by Wirth and Long []. While our starting isotropic model matched the radial component receiver functions well, we were unable to match features on the transverse component data that arrive between 3–6 s. We added a layer of anisotropy in the wedge mantle with a trench‐parallel fast symmetry axis, as inferred from previous studies [e.g., Long and van der Hilst , ; Nakamura and Yamamoto , ]. Although this feature improved the fit, we were unable to identify a combination of anisotropy parameters for the wedge mantle portion of our model that allowed us to reproduce all the transverse component features.…”
Section: Forward Modelingmentioning
confidence: 99%
“…[5] Previous shear wave splitting studies in Ryukyu have reported strong mantle wedge anisotropy, with delay times of~1 s [e.g., Long and van der Hilst, 2006;Nakamura and Yamamoto, 2009]. The subducting slab beneath the stations used in these studies is relatively shallow (~40 km) [Syracuse and Abers, 2006], and accruing a shear wave splitting delay time of~1 s would require the presence of strong anisotropy.…”
Section: Introductionmentioning
confidence: 99%